2005
DOI: 10.1007/s10008-005-0033-7
|View full text |Cite
|
Sign up to set email alerts
|

RuO2 electrode surface effects in electrocatalytic oxidation of glucose

Abstract: We have studied the electrocatalytic activity of RuO2-PVC film electrodes, fabricated using RuO2 powders prepared at five different temperatures, viz., 300, 400, 500, 600 and 700 degrees C, for the oxidation of glucose in high alkaline media, 1 to 3 M NaOH. The RuO2-PVC film electrodes have been first characterized in 1 to 3 M NaOH solution by cyclic voltammetry (CV) and rotating disc electrode (RDE) techniques in a wide potential range -1,100 to 450 mV (SCE), and three redox pairs representing Ru(IV)/Ru(III),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 35 publications
6
34
1
Order By: Relevance
“…Linear E p vs. pH plots were obtained for experiments in acetate and phosphate buffers at pH values between 4.0 and 8.0. The slope of such representations for all peaks was 55±10 mV/decade, suggesting, in agreement with literature for the electrochemistry of transition metal oxides [48][49][50], that equal numbers of protons and electrons are involved. Although the standard potential for the process…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Linear E p vs. pH plots were obtained for experiments in acetate and phosphate buffers at pH values between 4.0 and 8.0. The slope of such representations for all peaks was 55±10 mV/decade, suggesting, in agreement with literature for the electrochemistry of transition metal oxides [48][49][50], that equal numbers of protons and electrons are involved. Although the standard potential for the process…”
Section: Resultssupporting
confidence: 69%
“…(−1.45 V vs. SHE; [51]) would make it possible that a complete reduction to Zr could occur, it is more reasonable to assume a stepwise reduction of the zirconia similar to what has been observed for Ru oxide [52]. The observed rather reversible behavior denotes that the structure of the parent oxide is not seriously affected so that the reduction of zirconias can be described either as a stepwise reduction to different suboxides or the reduction to one suboxide but of differently sized particles.…”
Section: Electrochemistry Of Undoped Zirconiasmentioning
confidence: 96%
“…Finally, the catalyst was regenerated back to the active form using an applied potential of 1.06 V (vs. Ag/ AgCl), as shown in Scheme 4, at an electrochemical rate constant of k' ME . Similar kinetic studies have already demonstrated for the ethanol oxidation at mvRuOxRuCN (in acidic solution) [30], glucose oxidation at RuO 2 (in alkaline condition) [11,13], and many biological molecules using lead ruthenate pyrochlore (under wide pHs) [54] Table 3 and earlier MM kinetics results at other RuOx-based systems are also shown for comparison. The catalytic rate constant k c is very close to earlier glucose oxidation results at graphite-epoxy RuO 2 (450 8C) composite and PVC-RuO 2 (300 8C) electrodes at strong alkaline conditions [11,13].…”
Section: Kinetic Analysismentioning
confidence: 52%
“…Ag=AgCl (0.22)] was used for adjusting the potential between E Ag/AgCl and E RHE , so that the pH-dependent ruthenium oxide redox potentials can be compared to the reported standard redox potentials of ruthenium in RHE (where Figure 1A shows the CV responses using PB/SPE, RuOx/ SPE, SPE in 2 mM Ru(CN) 4À 6 , and mvRuOx-RuCN/SPE in the presence and absence of glucose in pH 2 Na 2 SO 4 [45,46], and this is indeed the case for the well-established RuOx mediation in alkaline condition [11,13]. Yet, the mediated oxidation of glucose in acidic media using the mvRuOxRuCN analogue is quite unique and thus it is suspected that different RuOx sites in the mvRuOx-RuCN network may play a role in catalysis.…”
Section: Electrode Preparationmentioning
confidence: 86%
“…As a result of the disproportion reaction, the oxy/hydroxy-Ru VII always transforms to lower oxidation states when pH < 12 [18 ± 20, 29]. Regarding to the specific redox oxidations, oxy/ hydroxy-Ru VI can oxidize aliphatic alcohols (e.g., ethanol) and formaldehyde in a wide pH range of 1 ± 14 [25, 28, 41 ± 43]; while the oxy-Ru VII can even mediate the carbohydrates (e.g., glucose) and aromatic alcohols (e.g., benzyl alcohol) oxidations under strong alkaline conditions [20,26,27,29,43]. The carbohydrate oxidation was chosen in his study to specific account for the presence of oxy-Ru VII since benzyl alcohol has solubility problem in aqueous solution [43].…”
Section: Introductionmentioning
confidence: 99%